Step * 1 1 1 1 1 2 2 2 of Lemma cWO-induction-extract-sqequal


1. Base
2. Base
3. ~ λf,bar_recursion,n,s. case if (0) < (n)
                                     then if (n 1) then inr p.let _,_ in Ax)  else inl <Ax, Ax> fi 
                                     else (inr p.let _,_ 
                                                   in Ax) )
                             of inl(r) =>
                             λa.let _,_ 
                                in Ax
                             inr(r) =>
                             λa.(f s1.(bar_recursion (n 1) m.if m=n  then inl a  else (s m)) s1)))
4. : ℤ
5. j ≠ 0
6. 0 < j
7. ∀t,s1:Base. ∀n:ℕ+. ∀x:Base.
     (G (G f^j 1 ⊥m.if m=n 1  then inl t  else (x m)) s1 ≤ s1 fix((λF,t. (f F))))
8. Base
9. s1 Base
10. : ℕ+
11. Base
12. 0 < n
13. is-exception(λs1@0.(G (G f^j 1 ⊥(n 1) m.if m=n  then inl s1  else if m=n 1  then inl t  else (x m)) 
                        s1@0))
⊢ λs1@0.(G (G f^j 1 ⊥(n 1) m.if m=n  then inl s1  else if m=n 1  then inl t  else (x m)) s1@0) 
  ≤ fix((λF,t. (f F)))
BY
(RW (SweepUpC UnrollRecursionC) THEN Reduce THEN SqLeCD) }

1
1. Base
2. Base
3. ~ λf,bar_recursion,n,s. case if (0) < (n)
                                     then if (n 1) then inr p.let _,_ in Ax)  else inl <Ax, Ax> fi 
                                     else (inr p.let _,_ 
                                                   in Ax) )
                             of inl(r) =>
                             λa.let _,_ 
                                in Ax
                             inr(r) =>
                             λa.(f s1.(bar_recursion (n 1) m.if m=n  then inl a  else (s m)) s1)))
4. : ℤ
5. j ≠ 0
6. 0 < j
7. ∀t,s1:Base. ∀n:ℕ+. ∀x:Base.
     (G (G f^j 1 ⊥m.if m=n 1  then inl t  else (x m)) s1 ≤ s1 fix((λF,t. (f F))))
8. Base
9. s1 Base
10. : ℕ+
11. Base
12. 0 < n
13. is-exception(λs1@0.(G (G f^j 1 ⊥(n 1) m.if m=n  then inl s1  else if m=n 1  then inl t  else (x m)) 
                        s1@0))
14. s1@0 Base
⊢ (G f^j 1 ⊥(n 1) m.if m=n  then inl s1  else if m=n 1  then inl t  else (x m)) s1@0 ≤ s1@0 
                                                                                                     fix((λF,t. (f F))\000C)


Latex:


Latex:

1.  f  :  Base
2.  G  :  Base
3.  G  \msim{}  \mlambda{}f,bar$_{recursion}$,n,s.  case  if  (0)  <  (n)
                                                                        then  if  s  (n  -  1)
                                                                                  then  inr  (\mlambda{}p.let  $_{}$,$_{\mbackslash{}\000Cff7d$  =  p 
                                                                                                            in  Ax) 
                                                                                  else  inl  <Ax,  Ax>
                                                                                  fi 
                                                                        else  (inr  (\mlambda{}p.let  $_{}$,$_{}\000C$  =  p 
                                                                                                    in  Ax)  )
                                                        of  inl(r)  =>
                                                        \mlambda{}a.let  $_{}$,$_{}$  =  r 
                                                              in  Ax
                                                        |  inr(r)  =>
                                                        \mlambda{}a.(f  a 
                                                                (\mlambda{}s1.(bar$_{recursion}$  (n  +  1)  (\mlambda{}m.if  m=n    then\000C  inl  a    else  (s  m))  s1)))
4.  j  :  \mBbbZ{}
5.  j  \mneq{}  0
6.  0  <  j
7.  \mforall{}t,s1:Base.  \mforall{}n:\mBbbN{}\msupplus{}.  \mforall{}x:Base.
          (G  f  (G  f\^{}j  -  1  \mbot{})  n  (\mlambda{}m.if  m=n  -  1    then  inl  t    else  (x  m))  s1  \mleq{}  f  s1  fix((\mlambda{}F,t.  (f  t  F))))
8.  t  :  Base
9.  s1  :  Base
10.  n  :  \mBbbN{}\msupplus{}
11.  x  :  Base
12.  0  <  n
13.  is-exception(\mlambda{}s1@0.(G  f  (G  f\^{}j  -  1  \mbot{})  (n  +  1) 
                                                (\mlambda{}m.if  m=n    then  inl  s1    else  if  m=n  -  1    then  inl  t    else  (x  m)) 
                                                s1@0))
\mvdash{}  \mlambda{}s1@0.(G  f  (G  f\^{}j  -  1  \mbot{})  (n  +  1) 
                  (\mlambda{}m.if  m=n    then  inl  s1    else  if  m=n  -  1    then  inl  t    else  (x  m)) 
                  s1@0)  \mleq{}  fix((\mlambda{}F,t.  (f  t  F)))


By


Latex:
(RW  (SweepUpC  UnrollRecursionC)  0  THEN  Reduce  0  THEN  SqLeCD)




Home Index